1990
DOI: 10.1007/bf00236696
|View full text |Cite
|
Sign up to set email alerts
|

Physiological differences between black and white runners during a treadmill marathon

Abstract: To determine why black distance runners currently out-perform white distance runners in South Africa, we measured maximum oxygen consumption (VO2max), maximum workload during a VO2max test (Lmax), ventilation threshold (VThr), running economy, inspiratory ventilation (VI), tidal volume (VT), breathing frequency (f) and respiratory exchange ratio (RER) in sub-elite black and white runners matched for best standard 42.2 km marathon times. During maximal treadmill testing, the black runners achieved a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
75
4
4

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 10 publications
7
75
4
4
Order By: Relevance
“…However, despite a similar resting blood lactate concentration and no significant difference in absolute power output, Caucasians had a significantly higher blood lactate concentration than black Africans during the fv exercise test from 4 kg to F Pmax + 1 kg. Lower blood lactate accumulation in black Africans (compared with Caucasians) has previously been reported during intense, continuous exercise [4,31]. However, this is the first time that this result has been reported for an intermittent sprint exercise.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…However, despite a similar resting blood lactate concentration and no significant difference in absolute power output, Caucasians had a significantly higher blood lactate concentration than black Africans during the fv exercise test from 4 kg to F Pmax + 1 kg. Lower blood lactate accumulation in black Africans (compared with Caucasians) has previously been reported during intense, continuous exercise [4,31]. However, this is the first time that this result has been reported for an intermittent sprint exercise.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, Coetzer et al [8] also reported that the plasma lactate concentration was significantly lower in the black African runners at two submaximal running workloads, despite an O 2 consumption similar to that seen in the Caucasian runners. Lower lactate accumulation has also consistently been reported in studies of black African runners [4,31] and elite Kenyan runners [26], compared with Caucasian runners.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Proposed explanations have included environmental factors (Saltin, 1996;Scott et al, 2003), psychological advantage (Baker & Horton, 2003) and favourable physiological characteristics that could be genetically conferred or environmentally determined (for a review, see Larsen, 2003). Some studies have also compared the physiological characteristics of ''black'' and ''white'' runners, reporting for the former lower blood and muscle lactate concentrations at a given exercise intensity (Coetzer et al, 1993;Saltin et al, 1995;Weston, Karamizrak, Smith, Noakes, Myburgh, 1999), better running economy (Saltin et al, 1995;Weston, Mbambo, & Myburgh, 2000) and an ability to tolerate higher fractional utilization of maximal oxygen uptake ( _ V O 2max ) (Bosch, Goslin, Noakes, & Dennis, 1990;Coetzer et al, 1993;Weston et al, 2000). However, the validity of extrapolating such findings to account for the success of East African athletes is questionable when participants have been classified into groups based primarily on skin colour, given that there are more genetic differences within ''race'' groups than between them (Yu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%